2014
DOI: 10.5935/0103-507x.20140028
|View full text |Cite
|
Sign up to set email alerts
|

High-volume hemofiltration and prone ventilation in subarachnoid hemorrhage complicated by severe acute respiratory distress syndrome and refractory septic shock

Abstract: We report the successful treatment of two patients with aneurismal subarachnoid hemorrhage complicated by severe respiratory failure and refractory septic shock using simultaneous prone position ventilation and high-volume hemofiltration. These rescue therapies allowed the patients to overcome the critical situation without associated complications and with no detrimental effects on the intracranial and cerebral perfusion pressures. Prone position ventilation is now an accepted therapy for severe acute respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Hemofiltration has been proposed as a possible therapeutic option to improve oxygenation by promoting fluid removal, but its efficacy remains controversial. Several studies have concluded that continuous renal replacement therapy (CRRT), indicated for acute fluid overload (FO) and acute renal failure, improves oxygenation in patients with respiratory failure, hypoxia, and fulminant hepatitis [12][13][14][15][16][17][18]. However, others found no improvement in oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…Hemofiltration has been proposed as a possible therapeutic option to improve oxygenation by promoting fluid removal, but its efficacy remains controversial. Several studies have concluded that continuous renal replacement therapy (CRRT), indicated for acute fluid overload (FO) and acute renal failure, improves oxygenation in patients with respiratory failure, hypoxia, and fulminant hepatitis [12][13][14][15][16][17][18]. However, others found no improvement in oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of HIC postoperative can present as a mass lesion (hematoma); Edema; Increased cerebral blood volume (vasodilation); LCR disorders. 5,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The most commonly used technique in clinical practice to monitor the peak involves an intraventricular or intraparenchymal catheter system, which is still considered the gold standard for monitoring ICP. These advances in PIC monitoring technique provides a variety of methods to assess ICP.…”
Section: Resultsmentioning
confidence: 99%
“…In summary the possible effects adeversos stand out as isquemia cerebral, 6,13 hypoxia/hypoxemia cerebral, [14][15][16][17][18][19][20][21][22] febre, 6,15 cerebral, [13][14][15][23][24][25] herniation, interference bloodstream/delay intracraniano, 14 blood flow, decreased perfusão, 14 pressure obstruction venoso, 14 reflux renal, 15 failure, hiperglicemia, [26][27][28][29][30][31] hipoglicemia, 26 death/ encefálica, 15,19,22 death, infection due to insertion of the catheter for monitoring PIC, 17,20,29 line offset média, 17 Hematoma, 17,19,29 intracerebral hemorrhage, 17,18,[20][21][22][23]30,31 secundária brain injury, 18 edema ...…”
Section: Resultsmentioning
confidence: 99%
“…Trauma (epidural and subdural hematoma, brain contusion); nontraumatic intracerebral hemorrhage;BIRD; hydrocephalus;HICbenign or idiopathic; other (pseudotumor cerebri, pneumoencéflo, cysts and abscesses, brain). 6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The main secondary causes (extracranial) are airway obstruction; Hypoxia or hypercapnia or hypercarbia (hypoventilation); Hypertension (pain / cough) and hypotension (hypovolemia / sedation); Posture of the patient (head rotation); hyperpyrexia; seizures; And metabolic drugs (e.g., tetracycline, rofecoxib, divalproex sodium, lead poisoning); Others (eg, cerebral edema high altitude, liver failure). The causes of HIC postoperative can present as a mass lesion (hematoma); Edema; Increased cerebral blood volume (vasodilation); LCR disorders.…”
Section: Resultsmentioning
confidence: 99%